Pengaruh Kreativitas dan Motivasi Belajar terhadap Hasil Belajar Matematika Berdasarkan Gaya Belajar Siswa di Kelas VIII Smp Negeri 7 Bulukumba - Hamzah Upu; Asdar; Ivan Adrian (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
This research was conducted to determine the effect of creativity and learning motivation on mathematics learning outcomes based on students' learning styles. This research is an ex-post facto research. This research was conducted at SMP Negeri 7 Bulukumba. Data collection techniques used learning style questionnaires, learning motivation questionnaires, learning creativity tests, andmathematics learning outcomes tests. The results of this research indicate that (1) students' learning styles are divided into visual and auditory learning style, (2) students' creativity based on visual and auditory learning style are in the good category, (3) students' learning motivation based on visual and auditory learning style is classified in the very good category, (4) learning outcomes of mathematics based on visual learning style are classified into the sufficient category, while based on auditory learning style are classified into good categories, (5) creativity and learning motivation have a joint effect on mathematics learning outcomes based on visual and auditory learning style, (6) creativity has a positive effect on mathematics learning outcomes based on visual and auditory learning style, (7) learning motivation has a positive effect on mathematics learning outcomes based on visual and auditory learning style.